Cooperative Learning Strategy Using Jigsaw Model in Nushus Learning of IDIA Students - Nurul Hidayati; Hendri Komara; Muhammad Waritsi; Solasi Haddiyanto (Maharot : Journal of Islamic Education, 2023)
Low learning quality is one of the problems facing the world of education today, such as the Nushus learning process. This lesson aims to find out how the lecturer uses cooperative learning strategies with the jigsaw model in classroom to improve student learning outcomes. Cooperative learning strategies are one way to make students' learning experiences more active in the classroom, this affects the development or abilities of students both in terms of cognitive and psychomotor. This study used a qualitative approach with observation and interview procedures to describe the overall learning process and evaluation process. Therefore, the objectives of this study are: to know the jigsaw cooperative learning model; and to know the advantages of the jigsaw type cooperative learning model compared to conventional learning models. The application of the jigsaw type cooperative learning model is effective for improving student learning outcomes, both learning outcomes in the cognitive, affective, and psychomotor domains. The results of this study indicate that learning using the cooperative strategy of the jigsaw model improves the learning outcomes of male intensive students at IDIA Prenduan.